The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/bbb.2058
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigation of succinic acid production by Actinobacillus succinogenes: a promising native succinic acid producer

Abstract: The biological production of succinic acid has attracted a great deal of attention due to the depletion of fossil fuels and concerns regarding environmental issues. As a natural producer of succinic acid, Actinobacillus succinogenes is one of the most promising candidates owning to its high production capability, wide carbon utilization spectrum, and robustness to environmental factors. This review details current achievements attempting to improve the efficiency of succinic acid production, not only in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 81 publications
(84 reference statements)
1
32
0
Order By: Relevance
“…A distinctive capacity to utilize a broad spectrum of carbon sources, including monosaccharides, both pentoses and hexoses, disaccharides, and polyhydroxy alcohols, is one of the most significant features for industrial producers of bulk chemicals [2]. Biochemical tests based on the API 50CHE system revealed that the Enterobacter sp.…”
Section: Transport and Metabolism Of Carbon Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…A distinctive capacity to utilize a broad spectrum of carbon sources, including monosaccharides, both pentoses and hexoses, disaccharides, and polyhydroxy alcohols, is one of the most significant features for industrial producers of bulk chemicals [2]. Biochemical tests based on the API 50CHE system revealed that the Enterobacter sp.…”
Section: Transport and Metabolism Of Carbon Sourcesmentioning
confidence: 99%
“…LU1 is a Gram-negative, rod-shaped, wild-type bacterium that has been isolated from goat rumen by bacterial enrichment and selective culture for succinic acid (SA)-producing bacteria [1]. SA, with a molecular formula of C 4 H 6 O 4 , is natural organic acid that exists in animals, plants, and microorganisms [2]. It has been recognized as one of the top 10 most promising C4-chemical building blocks with prospects for bio-based commercial production [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biotechnological production of succinic acid has been explored extensively using various biomass and agro-residues as precursors (e.g., sake lees, cane molasses, corn stover, corncob, bagasse, cassava root) (Yang et al 2019). However, only few attempts have been made using pineapple waste as the substrate for succinic acid production.…”
Section: Introductionmentioning
confidence: 99%